Service culture assessment focusing on the use value of medical records and health information in hajj general hospital Makassar city Indonesia - Muhammad Thabran Talib (Universitas Aisyah Pringsewu, 2023)
Health workers as one of the main components in providing health services to the community have a very important role because they are directly related to the quality of service. The purpose of this study was to determine the results of a service culture assessment that focuses on the use value of Medical Records and Health Information. The method used in this study was quantitative analysis, this study used a cross-sectional approach, from January to March 2022, with the inclusion criteria being Professional Caring Providers, a sample of 132 respondents consisting of 42 doctors and 90 nurses. The results of the study show that 84.54% of the caregivers have successfully implemented a culture of service. In the discussion, the new Professional Caring Provider implements a service culture that focuses on the use value of patient medical records, namely the lowest value is 15 and is not optimal. The non-optimal patient-focused service culture may be due to the fact that professional care givers have not received training, patients have waited a long time for service delivery, professional collaboration has not existed and the need to improve communication. Skills. A patient-focused service culture can work well if Caregiving Professionals are able to build trust from their patients with effective communication, empathy, and caring. Suggestion, it is necessary to increase socialization related to the implementation of instilling value for medical records to all parties involved in the patient information service process. Abstrak: Tenaga Kesehatan sebagai salah satu komponen utama dalam memberikan pelayanan kesehatan kepada masyarakat memiliki peran yang sangat penting karena berhubungan langsung dengan mutu pelayanan. Tujuan penelitian ini untuk mengetahui hasil penilaian budaya pelayanan yang menitikberatkan pada nilai guna Rekam Medis dan Informasi Kesehatan. Metode yang digunakan dalam penelitian ini adalah dengan analisis kuantitatif, penelitian ini menggunakan pendekatan cross-sectional, dari bulan Januari sampai Maret 2022, dengan kriteria inklusi adalah Professional Caring Provider, sampel sebanyak 132 responden yang terdiri dari 42 dokter dan 90 perawat. Hasil penelitian menunjukkan bahwa budaya pelayanan telah berhasil dilaksanakan oleh 84,54% Tenaga Pengasuh. Dalam pembahasannya, Professional Caring Provider yang baru menerapkan budaya pelayanan yang menitikberatkan pada nilai guna rekam medis pasien yaitu nilai terendah adalah 15 dan belum optimal. Budaya layanan yang berfokus pada pasien yang tidak optimal mungkin disebabkan oleh fakta bahwa pemberi perawatan profesional belum mendapatkan pelatihan, pasien telah menunggu lama untuk pemberian layanan, kolaborasi profesional belum terjalin dan kebutuhan untuk meningkatkan komunikasi keterampilan. Budaya pelayanan yang berfokus pada pasien dapat bekerja dengan baik jika Caregiving Professionals mampu membangun kepercayaan dari pasiennya dengan komunikasi, empati, dan kepedulian yang efektif. Saran, Perlu peningkatan sosialisasi terkait pelaksanaan penanaman nilai guna rekam medis kepada semua pihak yang terlibat dalam proses pelayanan informasi pasien.